Blood Lactate and Maximal Lactate Accumulation Rate at Three Sprint Swimming Distances in Highly Trained and Elite Swimmers - Maria Mavroudi; Athanasios Kabasakalis; Anatoli Petridou; Vassilis Mougios (MDPI AG, 2023)
We examined the blood lactate response, in terms of the maximal post-exercise concentration (Lamax), time to reach Lamax, and maximal lactate accumulation rate (VLamax), to swimming sprints of 25, 35, and 50 m. A total of 14 highly trained and elite swimmers (8 male and 6 female), aged 14-32, completed the 3 sprints in their specialization stroke with 30 min of passive rest in between. The blood lactate was measured right before and continually (every minute) after each sprint to detect the Lamax. The VLamax, a potential index of anaerobic lactic power, was calculated. The blood lactate concentration, swimming speed, and VLamax differed between the sprints (p < 0.001). The Lamax was highest after 50 m (13.8 ± 2.6 mmol·L-1, mean ± SD throughout), while the swimming speed and VLamax were highest at 25 m (2.16 ± 0.25 m·s-1 and 0.75 ± 0.18 mmol·L-1·s-1). The lactate peaked approximately 2 min after all the sprints. The VLamax in each sprint correlated positively with the speed and with each other. In conclusion, the correlation of the swimming speed with the VLamax suggests that the VLamax is an index of anaerobic lactic power and that it is possible to improve performance by augmenting the VLamax through appropriate training. To accurately measure the Lamax and, hence, the VLamax, we recommend starting blood sampling one minute after exercise.